FEATURES OF PREVENTION AND PHYSICAL TRAINING WITH OSTEOPOROSIS - Piven, O. P.; Polishchuk, V. V. (Rehabilitation and Recreation, 2022)
Today, osteoporosis is a systemic, progressive skeletal disease, accompanied by a decrease in bone massand disruption of bone microarchitecture, the appearance of fractures with minimal damage.The article outlines the main risk factors for osteoporosis. Modern laboratory biochemical diagnosticcomplexes and instrumental methods of studying the course of osteoporosis in citizens engaged in physicalactivity are described.Objective: to systematize modern knowledge about the processes of reducing the bone mineral densityof citizens in everyday life and exercise.Material. Methods of reaction of osteoporosis by means of factors of food and physical activityat the citizens who are engaged in fitness and various kinds of sports are offered. For prevention in the fieldof physical culture and sports it is necessary to use non-drug methods: balanced nutrition of athletes, med-ical control of training loads of athletes, enrichment of their body with sufficient vitamins and minerals.Results. An analysis of the literature revealed that there are two main types of osteoporosis: primaryand secondary. Primary osteoporosis usually develops in old age. Secondary osteoporosis is often the resultof metabolic, endocrine or hormonal disorders in the body. For the differential diagnosis of osteoporosis,the following are performed: laboratory tests of blood and urine; determination of the panel of phospho-rus-calcium metabolism and osteoporosis; instrumental research. The main signs of calcium deficiency inthe human body are described. The reasons for the decrease in bone mineral density in athletes have beenidentified. To prevent osteoporosis, the following are recommended: regular exercise and moderate muscletraining; training on special simulators; different types of physical activity. A diet that can seriously reducethe risk of osteoporosis was analyzed. The need to exclude from the diet foods that impair calcium absorp-tion or promote its leaching from the body is justified.Conclusions. In the field of physical culture and sports prevention of osteoporosis are: a balanced dietof athletes, medical control of training loads of athletes, providing their bodies with sufficient vitaminsand minerals. To prevent osteoporosis, regular exercise, moderate muscle load, and special exercises thattrain different muscle groups and slow bone loss are recommended.